PENERAPAN KEBIJAKAN NILAI UKHUWAH ISLAMIYAH PONDOK PESANTREN RIAB ACEH BESAR DALAM MENINGKATKAN HUBUNGAN SOSIAL SESAMA SANTRIWATI - Fatimah Chairil; Syahrul Riza; Syafruddin Syafruddin; Masbur Masbur; Mawardi Mawardi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to examine the implementation of ukhuwah Islamiyah values at RIAB Islamic you School in Aceh Besar and their role in enhancing social relationships among female students (santriwati). Ukhuwah Islamiyah which encompasses a sense of brotherhood, mutual respect, helping one another, and empathy among fellow Muslims is a fundamental principle in fostering harmonious social bonds within the pesantren environment. This research employs a descriptive qualitative method with a field study approach. Data were collected through observation, in-depth interviews with boarding school caretakers, teachers, and students, as well as documentation. The findings indicate that the values of ukhuwah Islamiyah are implemented through religious activities, character building, and exemplary behavior demonstrated by female teachers and dormitory supervisors. The implementation of these values has proven effective in fostering a sense of togetherness, reducing conflicts, and strengthening solidarity among the students. The study concludes that strengthening ukhuwah Islamiyah values has a significantly positive impact on the quality of social relationships among female students and can serve as a model for social development in Islamic boarding schools in general.